Compliance to Treatment Regimen among Hemodialysis Patients in Selected Private Tertiary Referral Hospitals in Kenya - Kilonzo, Gabriel Njuguna; Githinji, Elijah Mwangi; Makworo, Drusilla; Mergia, Ermias Terefe (International Journal of Health Sciences, 2025)
Purpose: This study aimed to evaluate the level of adherence to the hemodialysis treatment regimen including session attendance, medication use, fluid intake and dietary restrictions and to identify associated factors among End Stage Renal Disease Patients receiving maintenance hemodialysis in three selected facilities. Methodology: A mixed-method study was conducted between April and June 2024, involving 129 adult patients and 7 key informants. Participants were grouped into site A (Thika, n=54) and site B (Nairobi and Kisumu, n=75). Data collection included a modified End-stage Renal Disease Adherence Questionnaire (ESRD-AQ), a self-administered questionnaire, and interviews using a Key Informant Interview Guide. Data were analyzed using SPSS version 27 and N-VIVO version 11. Univariate variables were analyzed using measures of central tendency and dispersion, while binary and multivariate logistic regression were used to assess associations between independent and dependent variables, with statistical significance set at <0.05. Results: Adherence was low with 81.5% of patients at site A and 73.3% at site B demonstrating poor compliance. In site A, factors associated with compliance to HD were primary education (A.O.R=0.008, P=0.008), secondary education (A.O.R=0.040, P=0.028), and level of practice of HD treatment regimen (A.O.R=0.028, P=0.028). In site B, knowledge of HD treatment regimen (P=0.033) and practice of HD treatment regimen (P=0.038) were negatively linked to adherence. Unique contribution to theory, practice and policy: The study concluded that adherence to HD regimen was suboptimal, driven by modifiable factors such as education level, income, knowledge, and behavioral practices. The findings highlight the need for a structured, innovative training program targeting determinants like knowledge and practice of HD treatment regimen to improve compliance thereby enhancing patient outcomes and informing clinical practice and policy.